HUBUNGAN KUALITAS VISUAL LINGKUNGAN URBAN DAN PERSEPSI PENGGUNANYA - Karya Widyawati (LPPM, 2010)
Basically, Cities is human life expression that is manifested in the form of mass and space. According to Eko Budiardjo, cities is a stage of memory, a reflection of history from the citizen visually. In other hand, Historian Arnold Toynbee wrote that history itself is not important, it is important what people think this history. A true from interpretation above that idea or image of building is the same important as the building, so that it causes space consist of physical space and conceptual space. User perception to visual qualities of urban environment where he lives, describes user comprehension to the physical environment and then it becomes basic requirements of user psychology. Today Kayutangan Corridor is one of commerce district in the central city of Malang with its characteristic of colonial buildings. Activity occuring at Kayutangan Corridor is trading and serving activities as prime motivator of district. Beside that there are many public facilities to scale city. Kayutangan Corridor as a distric of design product that was a inheritence of Colonial government previously had been very harmonious. Emerging new buildings with modern architecture style and no environmental contex have caused to descend visual quality and to be lost identity taste for user. Objective of research is identification of design to describe how environment communicates messages for users, identification conformity of visual messages of design with users perception, and identification product of person perception and the influence to user response to the physical environment. Research is did with descriptive method by observation and using cognitive map as basic of analisis. Research about the users perception to environmental, will be expected to become point of departure planning and designing of corridor in the future. Key words : Visual quality of urban environment, users perception.